Designing Games for Ethics 2011
DOI: 10.4018/978-1-60960-120-1.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Quick Takes on Ethics and Games Voices from Industry and Academia

Abstract: In this chapter, seven experts from the games industry and from academia discuss late-breaking and big picture trends in ethics and games. Rather than deep analyses of the issues, these brief perspectives introduce main ideas related to current problems in ethics and games. These quick takes open up discourse on timely topics and ask questions that will lead to new research streams. A microcosm of the entire book, these quick reflections telegraph the themes that will emerge in the rest of the book. First, Mia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, a critical drawback of these resource-intensive practices, which often involved guidance from mentors or experts, is the limitation of the scalability ( Fleischmann et al, 2011 ; Saltz et al, 2019 ) and generalizability ( Ocholla, 2009 ) to meet the timely yet scattered, and professional yet interdisciplinary, needs of ethics education in different information practices. As a result, instructional environments and materials that can accommodate structural curriculum and self-directed learning at the same time are greatly needed ( Consalvo et al, 2011 ; Rush, 2014 ; Mora et al, 2017 ).…”
Section: Ethics Education For Information Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a critical drawback of these resource-intensive practices, which often involved guidance from mentors or experts, is the limitation of the scalability ( Fleischmann et al, 2011 ; Saltz et al, 2019 ) and generalizability ( Ocholla, 2009 ) to meet the timely yet scattered, and professional yet interdisciplinary, needs of ethics education in different information practices. As a result, instructional environments and materials that can accommodate structural curriculum and self-directed learning at the same time are greatly needed ( Consalvo et al, 2011 ; Rush, 2014 ; Mora et al, 2017 ).…”
Section: Ethics Education For Information Professionalsmentioning
confidence: 99%
“…Game-based learning meets the learning needs of contextual practices in information ethics education ( Fallis, 2007 ; Consalvo et al, 2011 ; McMenemy et al, 2014 ). The highly self-directed nature of playing games also provides both novice and expert learners with opportunities to learn and explore at their own paces ( Prensky, 2003 ; Rush, 2014 ).…”
Section: Serious Games For Information Ethics Educationmentioning
confidence: 99%
“…A lot of the behaviors portrayed or expected within games, such as lying, manipulating, scheming etc. (Consalvo et al , 2011) can affect players' behavior even outside of the games. This is especially concerning, considering the increase in applying psychological studies and behavioral economics into the design process of games.…”
Section: Gamingmentioning
confidence: 99%
“…These features were the most common and were found in 75% of the studied ecommerce websites. (Consalvo et al , 2011). However, their second study found that shoppers would rather be encouraged to make deliberate decisions rather than impulsive purchases, and wish for e-commerce sites to implement friction to their design in order to prevent them from spending an excessive amount of money (Moser et al , 2019)…”
Section: E-commercementioning
confidence: 99%